Secure MQTT PUF-Based Key Exchange Protocol for Smart Healthcare - Rizka Reza Pahlevi; Parman Sukarno; Bayu Erfianto (Universitas Syiah Kuala, 2021)
Replay and eavesdropping attacks threaten the information security that is held by smart healthcare devices. An authenticated key exchange method to provide cryptography sessions is the best way to provide information security and secure authentication. However, smart healthcare devices do not have sufficient computation to perform heavy cryptography processes due to the limitations of the embedded devices used. We propose an authenticated key exchange protocol based on a physical unclonable function (PUF). The proposed protocol aimed to countermeasure from replay and eavesdropping attacks. We designed our protocol with one handshake process and three authentication processes. We evaluated our proposed protocol using Tamarin Prover. From the results of the evaluation, our proposed protocol can exchange properties correctly between communication actors and is valid in proving each lemma in eavesdropping and replay attacks.